Adequacy of future retirement incomes: New evidence for private sector employees - Laurence O'Brien; David Sturrock; Jonathan Cribb (Institute for Fiscal Studies (IFS), 2024)
This report takes a fresh look at the prospects for the future of retirement incomes for employees in the UK. Since the Pensions Commission reported around 20 years ago, much has changed in the economic and pensions policy environment. While the introduction of automatic enrolment has been in many respects a great policy success - and the level and coverage of the flat-rate component of the state pension have increased markedly - lower-than-expected growth in earnings and depressed returns to saving make the private saving landscape more challenging. This report undertakes new modelling for those in paid employment today, simulating their future earnings until retirement and assuming that they continue to place the same share of those earnings in a pension as currently and that the new state pension will rise in line with earnings. We assess the outlook for whether people will reach the replacement rate targets set out by the Pensions Commission and whether they will reach the retirement living standards set out by the Pensions and Lifetime Savings Association (PLSA). We also show results from an economic model of when and how much people should save at different points in life.
Keywords: 330; Savings; pensions and wealth; Private pensions; Retirement; Savings